Barbados : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This report evaluates the stability of the financial system in Barbados. The findings reveal that Barbados has a relatively well developed financial system, including a large offshore sector. The onshore system is dominated by large, regionally active banks. Banking services to the population are also provided by the credit union sector. The system also includes a mature but concentrated insurance sector with extensive international affiliates, and other nonbank financial institutions provide credit and other instruments for savers. With a deteriorating fiscal situation and weak growth prospects, Barbados faces considerable macroeconomic vulnerabilities. Sovereign risk is a concern, given a large public debt, high fiscal deficits, and slow growth, and policy options are limited by a fixed exchange rate regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet